Un aspecto olvidado del «enigma Roncalli»: el pontificado de Juan XXIII y el estudio crítico de la Biblia - Ossándon, Juan Carlos 1976- (2024)
After the publication of Pius XII’s encyclical Divino Afflante Spiritu in 1943, modern biblical exegesis began to spread within the Catholic Church. Fifteen years later, the tides turned. During the pontificate of Pope John XXIII (1958-1963), the Holy Office took several restrictive measures, most notably the suspension of three professors. The article describes these interventions and asks whether the Pope promoted (or tolerated) this policy on biblical studies and why he did so. To do this, it uses some recent publications, among which Roberto Tucci’s diary stands out. It also attempts to reconstruct the general attitude towards the modern biblical exegesis of the Pope of the Second Vatican Council.
Keywords: Antonino Romeo; Concilio Vaticano II; Juan XXIII; Max Zerwick; Pontificia Comisión Bíblica; Pontificia Universidad Lateranense; Pontificio Instituto Bíblico; Roberto Tucci; Santislas Lyonnet; Santo Oficio; exégesis bíblica moderna